Unemployment and Property Crimes in Pakistan - Gillani, Syed Yasir Mahmood; Khan, Rana Ejaz Ali; Gill, Abid Rashid (Asian Economic and Financial Review, 2011)
The study examines the relationship between unemployment and property crimes for Pakistan covering the period of 1975 to 2008. The Johansen cointegratiom methodology along with Granger causality through VEC is applied to the annual time series data. The results of the cointegration analysis provide evidence of a valid long-run relationship between unemployment and different kinds of property crimes. The results provide evidence of unidirectional causality running from unemployed to different kinds of property crimes. The causality results explain that unemployment Granger cause theft, dacoity, robbery and cattle theft while it does not cause burglary.